2018
DOI: 10.1093/treephys/tpy084
|View full text |Cite
|
Sign up to set email alerts
|

Increased root investment can explain the higher survival of seedlings of ‘mesic’ Quercus suber than ‘xeric’ Quercus ilex in sandy soils during a summer drought

Abstract: In Mediterranean-type ecosystems, drought is considered the main ecological filter for seedling establishment. The evergreen oaks Quercus ilex L. and Quercus suber L. are two of the most abundant tree species in the Mediterranean Basin. Despite their shared evergreen leaf habit and ability to resist low soil water potentials, traditionally it has been suggested that Q. ilex is better suited to resist dry conditions than Q. suber. In this study, we examined how seedlings of Q. ilex and Q. suber grown in sandy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 89 publications
1
12
0
Order By: Relevance
“…2; Table S7). Previous studies have similarly reported higher sclerophylly for both oak populations and species inhabiting drier sites (Wright et al ., 2001; Niinemets, 2015; Ramírez‐Valiente et al ., 2015b; Ghouil et al ., 2020; Sancho‐Knapik et al ., 2021), with precipitation appearing as a major driver of the evolution of SLA and leaf thickness in species from seasonally‐dry ecosystems (Ramírez‐Valiente et al ., 2010, 2019). The functional basis of the association between sclerophylly and water limitation is under ongoing debate (but see Gil‐Pelegrín et al ., 2017; Alonso‐Forn et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…2; Table S7). Previous studies have similarly reported higher sclerophylly for both oak populations and species inhabiting drier sites (Wright et al ., 2001; Niinemets, 2015; Ramírez‐Valiente et al ., 2015b; Ghouil et al ., 2020; Sancho‐Knapik et al ., 2021), with precipitation appearing as a major driver of the evolution of SLA and leaf thickness in species from seasonally‐dry ecosystems (Ramírez‐Valiente et al ., 2010, 2019). The functional basis of the association between sclerophylly and water limitation is under ongoing debate (but see Gil‐Pelegrín et al ., 2017; Alonso‐Forn et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…(2013) in a study on P. pinaster populations growing in two common garden experiments found that root biomass was positively associated with T 50 (time at which populations reached 50% of mortality) and with the survival rate in the xeric common garden at the end of the experiment, supporting an adaptive role of root investment under dry conditions. The benefits of higher root investment are usually related to the fact that deep and well‐developed root systems increase access to groundwater and allow plants to maintain a better water status under low soil water potentials (Lloret et al., 1999; Markesteijn & Poorter, 2009; Ramírez‐Valiente et al., 2019). Consistent with these patterns, Matías et al.…”
Section: Reviewing the Evidence Of A Productivity‐persistence Trade‐o...mentioning
confidence: 99%
“…suber and Q. ilex. F v /F m has been employed as a parameter of Quercus performance under drought conditions [60,67], although in some cases different results when comparing species, e.g., Q. ilex and Q. suber, have been reported [68]. This can be due to either the severity of the stress, as well as the genotype, developmental stage, or the climate conditions employed.…”
Section: Photosynthesis Parameters In Droughted Quercus Seedlings and Tolerance Differencesmentioning
confidence: 99%